The interfacing structural effect of Ag/graphene oxide nanohybrid films on surface enhanced Raman scattering. Issue 18 (21st April 2017) - Kim, Young-Kwan; Ok, Gyeongsik; Choi, Sung-Wook; Jang, Hongje; Min, Dal-Hee
Abstract : The interfacing structural influence of Ag/GO nanohybrid films on their surface enhanced Raman scattering (SERS) was systematically investigated to reveal the details of the enhancement mechanism and develop an efficient SERS platform. Abstract : The interfacing structural effect of Ag/graphene oxide (GO) nanohybrid films on SERS was investigated by using Ag nanostructures immobilized on polyallylamine hydrochloride (PAA) functionalized-GO and reduced GO (RGO) films. We found that the electron transfer from Ag nanostructures to GO derivatives dominantly occurred at the interfaces between Ag nanostructures and the sp 2 carbon domains of GO and RGO films. By utilizing 4-aminothiophenol (4-ATP) as a Raman probe, it was revealed that this electron transfer process augmented the enhancement factor (EF) of 4-ATP up to ∼1.8 fold on Ag/PAA-RGO nanohybrid films compared to Ag/PAA-GO nanohybrid films with the increasing interfacing area between Ag nanostructures and the sp 2 carbon domains of GO derivatives through wet-chemical processes.